2018
DOI: 10.1037/xhp0000438
|View full text |Cite
|
Sign up to set email alerts
|

The speed of voluntary and priority-driven shifts of visual attention.

Abstract: (2018) 'The speed of voluntary and priority-driven shifts of visual attention.', Journal of experimental psychology : human perception and performance., 44 (1). pp. 27-37.Further information on publisher's website:https://doi.org/10.1037/xhp0000438Publisher's copyright statement:c 2017 APA, all rights reserved. This article may not exactly replicate the nal version published in the APA journal. It is not the copy of record. Use policyThe full-text may be used and/or reproduced, and given to third parties in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
(98 reference statements)
2
6
0
Order By: Relevance
“…While at the earlier intersaccadic intervals both neural representations are most likely to be active at the same time, the 190 ms time point reflects the moment when the new representation dominates the old representation on the oculomotor map. Interestingly, the time-course of updating of the competing representations in the oculomotor system is similar to the one reported in the studies investigating the time-course of shifts of covert spatial attention 35 , 36 . Given the close relationship between attention and eye movements, there is a possibility that these mechanisms are related 37 39 .…”
Section: Discussionsupporting
confidence: 78%
“…While at the earlier intersaccadic intervals both neural representations are most likely to be active at the same time, the 190 ms time point reflects the moment when the new representation dominates the old representation on the oculomotor map. Interestingly, the time-course of updating of the competing representations in the oculomotor system is similar to the one reported in the studies investigating the time-course of shifts of covert spatial attention 35 , 36 . Given the close relationship between attention and eye movements, there is a possibility that these mechanisms are related 37 39 .…”
Section: Discussionsupporting
confidence: 78%
“…Treisman and Souther (1985) found explaining slopes via variations in dwell time problematic because they observed target-absent slopes as shallow as 13 ms/item (see also Liesefeld et al, 2016, who found statistically significant target-absent slopes down to 2.9 ms/item), whereas traditional estimates of dwell time/shifts of attention are around 150-300 ms (Eriksen & Hoffman, 1972;Duncan, Ward, & Shapiro, 1994;Raymond, Shapiro, & Arnell, 1992;Theeuwes, Godijn, & Pratt, 2004;Ward, Duncan, & Shapiro, 1996. More recent evidence is indicative of shorter dwell times, of the order of 50-60 ms (Grubert & Eimer, 2016;Jenkins, Grubert, & Eimer, 2018), which might still be too long to explain some (barely) inefficient searches.…”
Section: Treisman's Responsementioning
confidence: 99%
“…Meanwhile, the Boolean map theory of attention suggests that features in the same dimension (e.g., different colors) can only be attended to one at a time Huang, Treisman, & Pashler, 2007;Morales & Pashler, 1999;Woodman & Luck, 2003). Thus, given a multiset display, the capacity of ensemble perception might be constrained by both (a) the rate of sampling and integrating individual objects in a set, which follows a temporal course at the millisecond scale, and (b) the speed of attending to and summarizing each set in a sequential manner, which requires shifts of attention that are suggested to have a time constant of ≤150 ms (Grubert & Eimer, 2016;Jenkins, Grubert, & Eimer, 2018;Woodman & Luck, 2003). In estimating the capacity of ensemble perception, effects of encoding speed need to be distinguished from effects of internal resource capacity.…”
Section: Capacity Limit Of Ensemble Perceptionmentioning
confidence: 99%